ENHANCEMENT OF A MICROFLUIDIC DEVICE SEEDED WITH CELLS VIA CFD ANALYSIS - Darbayeva, Elvira (Nazarbayev University School of Engineering and Digital Sciences, 2022)
Organ-on-a-chip technology can mimic the physiology of human organs and organ systems, help researchers better understand pharmaceutical drug effects on organisms before human clinical trials, and improve preclinical safety and efficacy of the drug testing. The key goal of this research is to use Computational Fluid Dynamics (CFD) techniques to evaluate the flooding properties of a microfluidic organ-on-a-chip device to enhance its functionality. The fundamental issue in the microfluidic chip design is the removal of entrained air bubbles that may remain after the fluid fills the chip, harming the cell observation process. This work aims to develop an enhanced microchip design utilizing CFD analysis to reduce entrained air while allowing proper residence time of the injected fluid and tolerable shear stress on the biological sample in the microfluidic chip. This thesis involved the creation of a CFD model on the ANSYS-CFX platform by discretizing the domain with the finite volume approach and solving the Navier–Stokes equations for air and water in the initial stage and water only in late-stage, in an Eulerian specification of the flow field.
Keywords: type of access: open access; CFD ANALYSIS; microfluidic device; Computational Fluid Dynamics; pharmaceutical drug effects; Organ-on-a-chip technology; human organs; ANSYS-CFX; pharmaceutical drug